Enhancing Moral Behavior: The Role of Religious Habituation and Technology-Assisted Supervision in Islamic Secondary Schools - Sutarman, Sutarman; Parjiman, Parjiman; Adi Kistoro, Hanif Cahyo; Hakim, Ahmad Luqman (Institut Studi Islam Muhammadiyah Pacitan, 2026)
The erosion of students’ moral values in the digital era has emerged as a critical challenge for Islamic secondary education, particularly in pesantren-based schools. Moral health, characterized by discipline, responsibility, honesty, and empathy, represents a crucial dimension of health behavior that supports a safe and conducive learning environment. Traditional supervision and religious habituation, while valuable, have proven insufficient to counter external negative influences without complementary approaches. This study aims to explore how the integration of pesantren-based religious values with Technology-assisted monitoring (IoT-Digital-Based Monitoring) can promote health behavior and strengthen moral health among students in Islamic schools. Using a qualitative case study design, research was conducted at Muhammadiyah Senior High School, Kasihan, Bantul, Yogyakarta, Indonesia. Data were collected through in-depth interviews, participatory observation, and school document analysis, and analyzed using the Miles and Huberman model with triangulation techniques. Findings indicate that the IoT-Digital-Based Monitoring significantly enhances students’ health behavior through improved discipline, responsibility, honesty, and empathy. The integration fosters a safer and more supportive school environment, reinforces moral norms, and facilitates behavioral self-awareness. Teachers and students reported positive perceptions of this synergy, with technology complementing traditional religious instruction. The Technology-assisted monitoring model offers an innovative intervention strategy for promoting moral health as part of broader health promotion efforts in Islamic schools. By combining formal technological control with informal religious guidance, this approach aligns with health promotion frameworks while preserving Islamic educational values. Broader adoption of such integrative strategies is recommended to adapt character education to the demands of the digital era.